ANALISIS KEMAMPUAN LITERASI NUMERASI SISWA SMP KRISTEN KALAM KUDUS AMBON - Ratumanan, Tanwey Gerson; Salamor, Reinhard; Mataheru, Eunike Ester (Program Studi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan Universitas Pattimura, 2022)
This study aims to identify students numeracy literacy capability. The research was conducted towards 8th grade student’s of Kristen Kalam Kudus Junior High School Ambon. Ever since 66 students, 20 students were randomly selected as research samples. The data collection was carried out using a numeracy literacy test instrument. To obtain data on the learning process in school, the development of numeracy literacy, was conducted using Learning Process Document wich was prepared by Mathematics Teacher. The data where analyzed using a five-scale conversion according to Ratumanan and Laurens (2015). The data review also where analyzed using qualitative descriptive analysis methods. According to this study, it was known, there are 2 students (10%) had a good numeracy literacy capability, 3 students (15%) had good numeracy literacy capability, 4 students (20%) had a sufficient literacy capability, 4 students (20%) have a deficient capability, meanwhile 7 students (seven) (35%) have a lower rate in literacy capability. The study from learning Process Document conducted by Mathematics Teacher, finding the result, which is : (1) The attention of the higher order thinking development has been accommodate. The result of this study can be seen in the formulation of objectives learning that accommodate the level of reasoning, the stages of learning accommodate the problem solving process, as well as practice questions and assessments that also accommodate the level of reasoning, (2) Implication of context in presenting the problem has been accommodated both in teaching materials and practice questions and tests, (3) the forms of questions/problems in learning and assessment are limited to multiple choice questions and descriptions. This shows that the efforts to develop numeracy literacy have been paid attention by the teacher, in despite of teacher's performance which has not been decent